Answer :
-899Kj
Explanation
ΔHrxn = ΔHproduct - ΔHreactant
ΔHrxn= {ΔHH2O(l) + ΔHCO2} - ΔHCH4
We do not put that of Molecular oxygen in the equation as it is zero
ΔHH2O(g) - ΔHH2O(l) = 44
-527 = {ΔHH2O(g) + ΔHCO2} - ΔH{CH2O}
-284 = {ΔHCH2O + ΔHH2O(g) } -ΔH{CH4}
Adding the last 2 equations together will yield the following:
-527-284 = 2ΔH{H2O}(g) + ΔHCO2 - ΔHCH4
From the second equation,
ΔHH2O(g) = 44 + ΔHH2O(l)
Substitute this in the added equation
-811 = 2(44 + ΔHH2O(l)) + ΔHCO2 - ΔHCH4
-811 = 88 + 2ΔHH2O(l) + ΔHCO2 - ΔHCH4
-899 = 2ΔHH2O(l) + ΔHCO2 - ΔHCH4
The heat of reaction is thus -899kJ